(untitled) (Research, Society and Development, 2023)
The present study aimed to outline the clinical-epidemiological profile of people living with HIV/AIDS (PLWHA) hospitalized with suspected COVID-19. This was a longitudinal, observational and retrospective study, through the analysis of clinical records of PLWHA, attended at the University Hospital Maria Aparecida Pedrossian, located in Campo Grande, MS, between March 2020 and December 2021. 92 cases of PLWHA who remained hospitalized for at least 24 hours, with suspected COVID-19, with dyspnea as the prevalent sign at hospital admission (70%). The sample (n=92) was divided into two groups: Group 1, composed of PLHA who tested positive for COVID-19 (n=23) and Group 2, composed of PLWHA who tested negative for COVID-19 (n=69). It was concluded that there was a predominance of men, aged between 44 and 53 years, in both groups. Patients admitted without COVID-19 had a worse immunosuppression condition (CD4+ levels < 200, detectable viral load and severe immunosuppression) and had a higher prevalence of opportunistic diseases. Similarly, both thought groups developed SARS, with saturation lower than 95%, need for ICU and need for IMV. As for the end, there was no difference between the groups.